Waging war - Lee, Wayne E., 1965- (Oxford)
xxi, 538 sayfa
Keywords: “Describes the emergence of military innovations and systems, examining how they were created and then how they moved or affected other societies. These innovations are central to most historical narratives, including the development of social complexity, the rise of the state, the role of the steppe horseman, the spread of gunpowder, the rise of the west, the bureaucratization of military institutions, the industrial revolution and the rise of firepower, strategic bombing and nuclear weapons, and the creation of “people's war““ --